2016
DOI: 10.4238/gmr.15017447
|View full text |Cite
|
Sign up to set email alerts
|

PDK2 and ABCG2 genes polymorphisms are correlated with blood glucose levels and uric acid in Tibetan gout patients

Abstract: ABSTRACT. Previous studies have shown that the PDK2 and ABCG2 genes play important roles in many aspects of gout development in European populations. However, a detailed genotype-phenotype analysis was not performed. The aim of the present study was to investigate the potential association between variants in these two genes and metabolismrelated quantitative phenotypes relevant to gout in a Chinese Tibetan population. In total, 316 Chinese Tibetan gout patients were recruited from rheumatology outpatient clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Statistical analyses were carried out using Microsoft Excel and SPSS 17.0 (SPSS, Chicago, IL, USA) software. Deviation from Hardy-Weinberg equilibrium (HWE) was tested for control subjects to measure the distribution of the polymorphism using a Chi-square test [ 42 ]. The Haploview software package (version 4.2) and SHEsis software platform ( http://analysis.bio-x.cn/myanalysis.php ) were used for analyses of linkage disequilibrium, haplotype construction [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analyses were carried out using Microsoft Excel and SPSS 17.0 (SPSS, Chicago, IL, USA) software. Deviation from Hardy-Weinberg equilibrium (HWE) was tested for control subjects to measure the distribution of the polymorphism using a Chi-square test [ 42 ]. The Haploview software package (version 4.2) and SHEsis software platform ( http://analysis.bio-x.cn/myanalysis.php ) were used for analyses of linkage disequilibrium, haplotype construction [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“… 59 , 60 Lack of association in African–Americans in GWAS is likely because of the reduced power because of lower allele frequency in African–Americans (≤3%) – there is nominal evidence for the association of the 141K variant with increased serum urate levels in African–Americans 18 and the increased risk of gout. 19 The Q141K variant (and other variants) has been associated with serum urate levels or hyperuricemia in other populations, for example, Tibetan 61 and Korean. 62 Uric acid transport assays in Xenopus oocytes showed that ABCG2 transports uric acid with the 141K variant causing ~50% reduced ability to secrete uric acid.…”
Section: Abcg2 Urate Control and Risk Of Goutmentioning
confidence: 99%
“…And exact test was carried out to confirm the compliance of SNP allele frequency with Hardy-Weinberg equilibrium (HWE). 19 The genotype and allele distributions were compared between the case and control groups by chi-square test. Associations of variations with individual NSCLC susceptibility, clinical characteristics and cisplatin combination chemotherapy response were examined using a logistic regression model.…”
Section: Discussionmentioning
confidence: 99%